Cut from the same cloth A study of female patrons in Luke-Acts and the Roman Empire - Miller, Amanda C. (2017)
This article discusses how women acted as patrons and benefactors in the social hierarchy of the Roman Empire, and how that sociohistorical context enlightens our understanding of women portrayed as patrons in the Gospel of Luke and Acts of the Apostles. Specifically in view are Mary Magdalene, Joanna, Susanna, and other unnamed women in Luke 8:1-3, and the businesswoman Lydia in Acts 16. Miller argues that Luke’s reading communities would have understood these women as important and influential members of the early Jesus movement, and that Luke blurs the lines between patron and client as part of his challenge to the Empire’s sociocultural boundaries.